Karakteristik Bahan Baku Artefak Batu di Situs Paroto, Situs Talepu, Situs Calio dan Situs Jampu : Sumber Gamping Kersikan: Karakteristik Bahan Baku Artefak Batu - Akram, Khairil; Makmur, Dwi Sumaiyyah (BRIN, 2025)
This research discuss about identification of raw materials for gravelly limestone artifacts in Walennae Valley area as the oldest settlement in Sulawesi with dating from 200.000 years ago. The method used for this research are library and field research (survey and interview) and also 3-dimensional recording. Data processing includes morphological-technological and petrological analysis with two analysis models, namely thin section analysis and spectrometric analysis on stone artifact samples. The results show that the morphological-technological material of limestone artifacts consists of two categories, core tools and retouched flakes. The identification of the limestone raw materials describe the process of limestone formation that occurs due to the transformation and weathering of CaCO3 compounds (calcite minerals) to form SiO2 compounds (silica minerals). In Walennae Valley, the human adaptation in utilizing and exploiting the raw materials for stone artifacts greatly influenced by the natural and environmental conditions of tropical forests.